Consider it done! Plan making can eliminate the cognitive effects of unfulfilled goals. [article]. - Masicampo, E. J.
Unfulfilled goals persist in the mind, as asserted by ample theory and evidence (e.g., the Zeigarnik effect). The standard assumption has been that such cognitive activation persists until the goal is fulfilled. However, we predicted that contributing to goal pursuit through plan making could satisfy the various cognitive processes that usually promote goal pursuit. In several studies, we activated unfulfilled goals and demonstrated persistent goal activation over time. Unfinished goals caused intrusive thoughts during an unrelated reading task. (Study 1 and 5B), high mental accessibility of goal-related words (Studies 2and 3), and poor performance on an unrelated anagram task(Study 4). Allowing participants to formulate specific plans for their unfulfilled goals eliminated the various activation and interference effects. Reduction of the effects was mediated by the earnestness of participants' plans: Those who untimately executed their plans were those also exhibited no more intrusions (Study 4). Moreover, changes in goal-related emotions did not appear to be a necessary component of the observed cognitive effects (Studies 5A and 5B). Committing to a specific plan for a goal may therefore not only facilitate attainment of the goal but may also free cognitive resources for other pursuits. Once a plan is made, the drive to attain a goal is suspended-allowing goal-related cognitive activity to cease-and is resumed at the specific later time.-(From the authors)